Strategi Bauran Komunikasi Pemasaran Produk Yamaha NMAX Turbo 2024 - Sudi, Mohamad; Zulham,; Maida, Serepina Tiur; Ningsih, Titiek Surya; Setianti, Yanti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The study aims to determine the marketing communication mix strategy implemented by Yamaha in promoting the 2024 NMAX Turbo product in Indonesia. To differentiate, Yamaha leverages six key marketing communication elements: advertising, sales promotion, public relations, direct marketing, personal selling, and digital marketing. Using a qualitative case study approach, data was gathered through in-depth interviews with Yamaha’s marketing managers, advertising agencies, and automotive influencers, as well as document analysis of annual reports and social media content. Thematic and content analysis were employed to interpret the data. Findings show that advertising played a significant role in building brand awareness through television and digital platforms, emphasizing the motor’s turbocharged technology and futuristic design. Sales promotions, particularly exclusive discounts and pre-order bonuses, effectively boosted consumer interest. Public relations initiatives, including launch events and test rides, enhanced the brand’s image and engagement. Direct marketing via email and SMS reinforced consumer relationships, while personal selling at dealerships offered a personalized experience. Digital marketing through platforms like Instagram and TikTok successfully reached younger audiences. This marketing mix strategy has proven effective in raising brand awareness, strengthening engagement, and driving sales for Yamaha.
Keywords: Marketing Communication Mix; Yamaha NMAX Turbo 2024